Valuing conservation and natural wealth: The blue economy of manta ray watching in the Maldives - Hannah M. Moloney; Maria I. Garcia Rojas; Nina Rothe; Asia O. Armstrong; Kirsty Ballard; Florence Barraud; Farah Hamdan; Anthony J. Richardson; Enas Mohamed Riyad; Tamaryn J. Sawers; Kathy A. Townsend; Guy M. W. Stevens (PLoS ONE, 2026)
Amid declining manta ray populations globally, the well-established and growing manta ray tourism industries generate substantial economic benefits and aid protective legislation for these threatened elasmobranchs. As flagship species, manta rays are a drawcard for marine wildlife tourism and a gateway for engaging the public and communities in conservation. Healthy marine ecosystems are the key drivers of employment and economic sustainability for island nations such as the Maldives. However, there are many stakeholders competing for these shared resources, which can result in environmental degradation. Economic valuations are a powerful tool for justifying the conservation efforts of threatened species and natural areas, especially in light of competing stakeholders. Using tour operator surveys ( n = 106) and data mining, this study provides an updated assessment of manta ray watching tourism in the Maldives and represents the first national valuation of its direct economic and socio-economic benefits. In 2021, manta ray tourism in the Maldives generated an estimated US$227.3 million, including US$39 million on manta ray focused diving and snorkelling excursions, and US$188.3 million in related tourist expenditure, representing 2.6% of the national Gross Domestic Product. This industry appears to have grown around 380% since 2008 (US$8.1 million) and manta ray watching is now offered by 80% of tourism operators nation-wide. Our findings revealed that manta rays hold intrinsic value and cultural significance within local communities. Acknowledging this, the flow-on benefits to the community extend beyond this industry, reaching local businesses, employed staff, and the government with the direct economic benefits of the manta ray tourism industry are estimated at over US$311 million per year. Such value highlights the significance of manta rays for the Maldives and the need for effective management centred on manta ray conservation to safeguard future prosperity and mitigate the potential impact of tourism on manta ray populations.